A new species of Conognatha Eschscholtz, 1829 (Coleoptera: Buprestidae), with new state records of the genus for Brazil - Pineda, Cristian; Barros, Rafael C.; Koike, Ricardo M. (Zootaxa, 2018)
Conognatha (Pithiscus) mielkei Pineda, Barros and Koike n. sp. (Coleoptera: Buprestidae), from southeast Brazil is described and illustrated. We also report five new state records for Brazil for the following species: Conognatha (C.) ovatula, Conognatha (P.) apicalis, C. (P.) excellens, C. (P.) insignis and C. (P.) sellovii.